Age — a significant independent factor of A1C levels. Evidence from the National Health and Nutrition Examination Survey 1999–2014. Issue 5 (October 2020) - Wang, Yanning; Wang, Dong; Liang, Hong; He, Jing; Luu, Sue-Wei; Bray, Christopher L.
Highlights: Age is a significant independent factor of A1C levels. A1C is significantly positively associated with age. A1C levels would increase by 0.009% (about 0.09 mmol/mol) in female and by 0.008% (about 0.08 mmol/mol) in male per year. Application of age-adjusted A1C level will improve patient safety. Abstract: Aim: The aim of our study is to examine the association between age and A1C levels in nondiabetic subjects and develop the age-adjusted A1C levels for screening and diagnosis of prediabetes and diabetes. Methods: Participants from National Health and Nutrition Examination Survey (NHANES) -1999–2014 with age over 12 years were examined. Individuals with previous diagnosed diabetes, baseline anemia, established hemoglobinopathies, known liver or chronic kidney disease, and abnormal liver function tests or creatinine levels were excluded. Total 16949 subjects consisting of 8651 female subjects and 8298 male subjects were included in the analyses. Linear regression and multivariate regression analyses were performed to assess the relationship between A1C levels and age. Age adjusted A1C levels were determined. Results: Significant positive correlation between A1C and age was found in both female and male subjects in the fasting plasma glucose (FPG) interval between 4.4–7 mmol/L (80–126 mg/dL) (P < 0.0001). There was a linear correlation between A1C levels and age. Linear regression analysis suggested A1C levels rose by 0.009% (about 0.09 mmol/mol) in female and by 0.008% (about 0.08 mmol/mol) in male per year in subjects without abnormality in glucose homeostasis (p < 0.0001). Conclusions: Our study concluded that age is a significant independent factor of A1C levels.